Thriving in dry conditions: on the Neotropical spider genus Galapa (Araneae: Pholcidae) - Huber, Bernhard A.; Meng, Guanliang; García, Jimmy Cabra; Carvalho, Leonardo S. (Zootaxa, 2024)
The genus Galapa Huber, 2000 includes tiny spiders (body length <1.5 mm) restricted to semi-arid habitats. It has long been thought to be endemic to the Galapagos Islands until G. spiniphila Huber, 2020 was described from the Venezuelan Paraguaná Peninsula. Here, we support this generic assignment with molecular (CO1) data and describe two new species from Colombia (G. gabito Huber sp. n.) and Costa Rica (G. murphyi Huber sp. n.), showing that the genus is actually widely distributed. Distribution modelling identifies several high suitability areas for Galapa, all of which are poorly sampled with respect to Pholcidae (ranging from Nicaragua to northern Peru and Guiana). Our results suggest a strong sampling bias against spiders restricted to dry tropical regions and habitats.